2013
DOI: 10.2174/1876386301306010023
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels in Visceral Pain

Abstract: Visceral pain is both different and similar to somatic pain - different in being poorly localized and usually referred elsewhere to the body wall, but similar in many of the molecular mechanisms it employs (like TRP channels) and the specialization of afferent endings to detect painful stimuli. TRPV1 is sensitive to low pH. pH is lowest in gastric juice, which may cause severe pain when exposed to the oesophageal mucosa, and probably works via TRPV1. TRPV1 is found in afferent fibres throughout the viscera, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 102 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…Of note, methylglyoxal (an endogenous carbonyl compound that is produced in large amounts during hyperglycemic conditions) activates human TRPA1 (Ohkawara et al ., ). Furthermore, TRPA1 has been implicated in migraine (Edelmayer et al ., ), dental pain (Haas et al ., ), chemotherapy‐induced neuropathic pain (Nassini et al ., ) and colicky pain of GI origin (Blackshaw et al ., ).…”
Section: Pain and Trp Channelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Of note, methylglyoxal (an endogenous carbonyl compound that is produced in large amounts during hyperglycemic conditions) activates human TRPA1 (Ohkawara et al ., ). Furthermore, TRPA1 has been implicated in migraine (Edelmayer et al ., ), dental pain (Haas et al ., ), chemotherapy‐induced neuropathic pain (Nassini et al ., ) and colicky pain of GI origin (Blackshaw et al ., ).…”
Section: Pain and Trp Channelsmentioning
confidence: 97%
“…TRP channels are widely expressed in the digestive tract, with important roles in taste, visceral sensation, GI motility, as well as absorptive and secretory functions (see Boesmans et al ., ; Holzer, ; Blackshaw et al ., ). Changes in TRP channel expression have been detected in a variety of GI ailments as exemplified by increased TRPV1 expression in both GERD (Matthews et al ., ; Bhat and Bielefeldt, ) and irritable bowel syndrome (Akbar et al ., ; Keszthelyi et al ., ).…”
Section: Inflammatory Bowel Disease (Ibd) and Trp Channelsmentioning
confidence: 97%
“…There is good evidence that TRP channels are involved in both of these processes (Fig. 25;see Holzer, 2004;Blackshaw et al, 2010Blackshaw et al, , 2013Holzer, 2011a,b).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…TRPA1 also has an influence on gastrointestinal motility (reviewed in Blackshaw et al, 2010Blackshaw et al, , 2013. TRPA1 agonists delay in vivo gastric emptying through serotonergic pathways.…”
Section: +mentioning
confidence: 99%
“…Indeed, several pharmaceutical companies have launched drug discovery programs aimed at the design and synthesis of potent and selective small molecule TRPA1 inhibitors as potential analgesic and anti-inflammatory agents [22,[28][29]. In preclinical future science group Patent Review Preti, Saponaro & Szallasi models, TRPA1 antagonists showed promise in diabetic neuropathy [22], dental pain [30], chemotherapy-mediated neuropathic pain [31] and colicky pain [32]. In addition, several lines of evidence implicates TRPA1 in the pathomechanism of migraine.…”
mentioning
confidence: 99%